Synthesis and Luminescence Properties of Core/Shell ZnS:Mn/ZnO Nanoparticles - Jiang Daixun; Cao Lixin; Liu Wei; Su Ge; Qu Hua; Sun Yuanguang; Dong Bohua (Nanoscale Research Letters, 2008)
Abstract In this paper the influence of ZnO shell thickness on the luminescence properties of Mn-doped ZnS nanoparticles is studied. Transmission electron microscopy (TEM) images showed that the average diameter of ZnS:Mn nanoparticles is around 14 nm. The formation of ZnO shells on the surface of ZnS:Mn nanoparticles was confirmed by X-ray diffraction (XRD) patterns, high-resolution TEM (HRTEM) images, and X-ray photoelectron spectroscopy (XPS) measurements. A strong increase followed by a gradual decline was observed in the room temperature photoluminescence (PL) spectra with the thickening of the ZnO shell. The photoluminescence excitation (PLE) spectra exhibited a blue shift in ZnO-coated ZnS:Mn nanoparticles compared with the uncoated ones. It is shown that the PL enhancement and the blue shift of optimum excitation wavelength are led by the ZnO-induced surface passivation and compressive stress on the ZnS:Mn cores.